The Use of Landsat TM in Assessing Forest Area Change in Selangor, Malaysia - Hamzah, Zulhazman (1999)
The rate of development due to industrialization and human settlement in the state of Selangor has accelerated tremendously in recent years, with a corresponding escalation in the rate of depletion of the forest areas. This trend has given rise to fears of impending depletion of forest areas and considerable concern for environmental stability and quality. Under these circumstances, the need for conservation and effective management of the forests in Selangor is imperative and cannot be under emphasized. One fundamental set of tools crucial in assessing forest cover changes will be the data provided by remote sensing. This study was undertaken to assess forest area changes in Selangor using satellite remote sensing technology. Detection of forest area change was performed using multitemporal LANDSAT data taken in 1993 and 1996, with the support of existing land use, topographic, and forest resource maps. The data were initially analyzed using Normalized Differences Vegetation Index (NDVI) in order to get a preliminary scenario of the change in forest cover. The data were then classified using Maximum Likelihood Classification (MLC) and Qvenaid to generate forest change. A total of 39 ground reference points were selected randomly and visited in ground truthing work. Results from this ground truthing showed that forest types can be identified and discriminated easily in LANDSAT TM data. The study quantified that within 1993 to 1996 the loss of inland forest was about 2824.5 ha which implies 941.5 ha per year of inland forest have been converted to other land use types. Peat-swamp forest and mangrove forest have also been reduced by 655.2 ha and 4738.5 ha, which account for an annual loss of 218.4 ha and 1579.5 ha, respectively. This means a total of 8218.2 ha of forest areas in Selangor have been converted to other land use types between 1993 to 1996, which implies an annual loss of about 2739.4 ha, with an accuracy of 84.2 percent. Factors causing forest cover changes include industries, human settlement, logging activities, aboriginal areas, agricultural, recreation and tourism, livestock and illegal settlement areas.